Editor’s Letter - González Alvarado, Tania Elena (Mercados y Negocios, 2025)
We are excited to share the 55th issue of Mercados y Negocios, which reflects our growing international reach. We sincerely want to thank the scientific community for its trust and support. As part of our commitment to fostering research and development, we remind our authors that Mercados y Negocios welcomes resubmission of rejected papers. This policy allows reviewers to provide feedback that helps authors refine their work and encourages a constructive dialogue to strengthen research contributions.